Pengembangan Instrumen Tes Kecerdasan Logika Matematika untuk Anak Sekolah Dasar di Kelas Rendah - Magdalena, Ina; Sari, Novia Permata; Hasanah, Nurul; Putri, Raafiza; Nurfitriah, Rachmah; Syaputri, Sekartini Rikawan (MASALIQ, 2023)
This research was deliberately carried out with the aim of producing a valid and reliable mathematical logical intelligence test instrument for elementary school children. there are three stages in the development instrument, namely: (1) Introduction, namely helping a problem and conducting a material study (2) Product development, namely compiling construct variables that are measured based on theory (3) Implementation scope, field trials, and conducting tests empirical, revising the items of the instrument, reaching the final instrument and carrying out the preparation of administrative guidelines and scoring. The tests that resulted from this study were one instruction sheet, items and pictures and an assessment sheet. The results of the validation show that the items have a significant level <0.05, with a reliability value of 0.856. Which shows that the intelligence test instrument on Logic-Mathematics is feasible to use.